Relationship between Protein Intake and Serum Albumin Levels in First Trimester Chronic Energy Deficient Pregnant Women in Padang City - Sonia Wulan Dari; Defrin; Mohamad Reza (Science Midwifery, 2021)
Albumin is a specific indicator to assess chronic energy deficiency (KEK) in pregnant women. Albumin functions as a protein that transports micronutrients in the blood. Low albumin levels can indicate KEK has occurred. This study aims to determine the relationship between protein intake and serum albumin levels for pregnant women in the first trimester of KEK in the city of Padang. This study was an observational correlative analytic study with a cross sectional approach. The sample in this study was 34 pregnant women in the first trimester of KEK with a proportional stratified random sampling technique. Interviews for protein intake using a modified semi quantitative food frequency questionnaire designed by Lipoeto were conducted at Pauh Puskesmas and Puskesmas Lubuk Kilangan while sample examinations were carried out at the Technical Implementation Unit of the West Sumatra Health Laboratory Service from June 2019 to November 2020. Data analysis used the Pearson correlation test. The results showed that the mean protein intake was 56.40 ± 14.612 g / day and the serum albumin level was 3.8 ± 0.604 g / dl. There is a significant relationship between protein intake (r = 0.467) and serum albumin levels. The conclusion is that there is a relationship between protein intake and serum albumin levels in pregnant women in the first trimester of SEZ in the city of Padang.